More green, fewer problems: landcover relates to perception of environmental problems. Issue 3 (5th January 2023) - Suchy, Amanda K; Anderson, Elsa C; Fork, Megan L; Lin, Laurence; Locke, Dexter H; Groffman, Peter M; Grove, J Morgan; LaDeau, Shannon L; Rosi, Emma J
Abstract : The relationship between (a) the structure and composition of the landscape around an individual's home and (b) environmental perceptions and health outcomes has been well demonstrated (eg the value of vegetation cover to well‐being). Few studies, however, have examined how multiple landscape features (eg vegetation and water cover) relate to perceptions of multiple environmental problems (eg air or water quality) and whether those relationships hold over time. We utilized a long‐term dataset of geolocated telephone surveys in Baltimore, Maryland, to identify relationships between residents' perceptions of environmental problems and nearby landcover. Residents of neighborhoods with more vegetation or located closer to water were less likely to perceive environmental problems. Water quality was one exception to this trend, in that people were more likely to perceive water‐quality problems when nearby water cover was greater. These trends endured over time, suggesting that these relationships are stable and therefore useful for informing policy aimed at minimizing perceived environmental problems.